Psychological factors associated with sensory processing sensitivity in caregiving contexts: A protocol for a systematic review and meta-analysis - Tadgh Connery; Megan Doyle; Mike Murphy; Annalisa Setti (PLoS ONE, 2025)
Background Caregiving, in both professional and informal settings, is a stressful role linked to burnout, anxiety and other negative mental health outcomes. Both environmental factors, such as perceived excessive workload and responsibility, interpersonal conflict, and poor communication, as well as personality factors, such as extraversion, agreeableness and neuroticism, have been associated with negative psychological outcomes in carers. Sensory Processing Sensitivity (SPS) is a temperament trait associated with poor mental health, characterised by high empathy and reactivity to environmental stimuli. Highly Sensitive People (HSPs) score highly in SPS and account for approximately 30% of the world’s population. SPS has been shown to be a marker of differential susceptibility, which predisposes individuals to feeling the harmful effects of negative environments and to flourish in positive ones. Given the stressful nature of both professional and informal caring environments, it is of interest to examine the experience of HSPs, those who score highly in SPS, within caregiving roles. The research examining SPS’ psychological correlates in caregivers has yet to be synthesised. The current study aims to systematically review the psychological correlates of SPS in caregiving populations and, where possible, to test the strength of these associations through meta-analysis. Method A systematic search of quantitative and mixed-methods studies, written in English and published since 1997, the year in which the HSP Scale was first validated, will be conducted across 11 databases: Web of Science, Scopus; EBSCO Academic Search Complete; APA PsycINFO; PubMed; MEDLINE; CINAHL Plus with Full Text; APA PsycArticles; Business Source Complete; SocINDEX with Full Text; and ERIC. Google Scholar will also be searched, and the first 200 records by relevance will be screened for eligibility. Forward and backward citation searches of included records will be also performed. MD will search for records, which will be screened for eligibility by MD and TC. Data extraction and quality assessment, using the Joanna Briggs Inventory Risk of Bias tool, will be performed by TC and MD, with doubts and discrepancies being resolved through discussion with AS and MM. Data will be synthesised narratively and, where sufficient data are available, correlational meta-analysis will be conducted using RStudio. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines were followed in the development of this protocol. The protocol has been registered in PROSPERO (CRD42024524463). Discussion This review will present a systematic overview of psychological factors associated with SPS in caregivers. It will identify psychological outcomes associated with SPS, as well as risk factors and protective factors that may be targeted to reduce negative outcomes for caregivers. Identifying these factors will allow for a better understanding of the HSPs’ experience of caregiving and consequently aid in enhancing this experience.